Δ‐Tocotrienol induces apoptosis, involving endoplasmic reticulum stress and autophagy, and paraptosis in prostate cancer cells. (4th February 2019) - Fontana, Fabrizio; Moretti, Roberta Manuela; Raimondi, Michela; Marzagalli, Monica; Beretta, Giangiacomo; Procacci, Patrizia; Sartori, Patrizia; Montagnani Marelli, Marina; Limonta, Patrizia
Abstract: Objectives: Prostate cancer, after the phase of androgen dependence, may progress to the castration‐resistant prostate cancer (CRPC) stage, with resistance to standard therapies. Vitamin E‐derived tocotrienols (TTs) possess a significant antitumour activity. Here, we evaluated the anti‐cancer properties of δ‐TT in CRPC cells (PC3 and DU145) and the related mechanisms of action. Materials and methods: MTT, Trypan blue and colony formation assays were used to assess cell viability/cell death/cytotoxicity. Western blot, immunofluorescence and MTT analyses were utilized to investigate apoptosis, ER stress and autophagy. Morphological changes were investigated by light and transmission electron microscopy. Results: We demonstrated that δ‐TT exerts a cytotoxic/proapoptotic activity in CRPC cells. We found that in PC3 cells: (a) δ‐TT triggers both the endoplasmic reticulum (ER) stress and autophagy pathways; (b) autophagy induction is related to the ER stress, and this ER stress/autophagy axis is involved in the antitumour activity of δ‐TT; in autophagy‐defective DU145 cells, only the ER stress pathway is involved in the proapoptotic effects of δ‐TT; (c) in both CRPC cell lines, δ‐TT also induces an intense vacuolation prevented by the ER stress inhibitor salubrinal and the protein synthesis inhibitor cycloheximide, together with increased levels of phosphorylated JNK and p38, supporting the induction of paraptosis by δ‐TT. Conclusions: These data demonstrate that apoptosis, involving ER stress and autophagy (in autophagy positive PC3 cells), and paraptosis are involved in the anti‐cancer activity of δ‐TT in CRPC cells.